Within language, beyond theories. - Bloch-Rozmej, Anna; Drabikowska, Karolina (Cambridge Scholars Publishing, 2015)
This is the second volume in a series of three books called Within Language, Beyond Theories, which focuses on current linguistic research surpassing the limits of contemporary theoretical frameworks in order to provide new insights into the structure of the language system and to offer more comprehensive accounts of linguistic phenomena from a number of the world's languages. The volume is composed of eighteen chapters, each focusing on a significant issue in the field of applied linguistic ...